EFFECT OF STOCKING DENSITY ON GROWTH PERFORMANCE AND SURVIVAL RATE OF ANGEL FISH (PTEROPHYLLUM ALTUM PELLEGRIN, 1930) - Loc, Ha Le Thi; My Dung, Nguyen Thi (Vietnam Journal of Marine Science and Technology, 2014)
Three-day-old Angel fishes (Pterophyllum altum) were utilized to investigate the effect of stocking density on their growth performance and survival rate. The fish were cultured in 25 liter, glass tanks at different treatments of density, including 5 individuals/L, 10 inds/L, 15 inds/L and 20 inds/L (triplicated). The results after 84 days showed that growth and survival rate of angel fish were significantly influenced by stocking density. The length and weight of fish reared at 5 inds/L (9.597±0.002 mm; 11.700± 0.1 g) were the best and significantly higher than fish in the treatment of 10 inds/L (9.167±0.058 mm; 11.067± 0.208g); 15 inds/L (7,699±0,03 mm; 10.933± 0,057 g) and 20 inds/L (4.928±0.004 mm; 7.900± 0.1g) (P<0.05). The survival rate of 5 inds/L treatment 85% was significantly higher than that of other treatments (10 inds/L: 80.0±0,5%; 15 inds/L: 77.0±0,57% and 20 inds/L: 74.6±0.38%). In combination of these two factors, the density of 5 inds/L is recommended in culture of three day old to three month old angel fishes.